Plant this, not that : over 200 native plant swaps for a more sustainable, pollinator-friendly garden - Howard, Elise (Native plant gardener) (Workman Publishing, 2026)
"These days, home gardeners know that many traditional, non-native garden plants--like English ivy, barberry, and burning bush--don't support our bees, butterflies, birds, and other creatures. And that native plants are more likely to thrive, because they evolved as part of the local ecology, so they often require less fussy maintenance and don't depend on pesticides and fertilizers. But gardeners ready to make the switch may ask: Where do I begin? And how do I find the best native plants for my landscape? PLANT THIS, NOT THAT considers some of the most common non-native (and often, invasive) plants in North American gardens and suggests substitutions for more beneficial and equally beautiful natives. Each native plant listing includes a full-color photo, along with sun, water, and soil requirements; ornamental features (including bloom time and color and whether the plant has berries, fruit, and/or fall color); and the pollinators known to depend on and support that plant. Accompanying maps show every plant's locally native range, down to the county level. The book also features an overview of how native plants contribute to our local ecosystems, where to shop for them, advice on maintaining a mostly native garden, and resources to learn more about native planting"--